A análise de conteúdo na prática pedagógica do ensino médio - Judice, Marcos Rodrigues (2019)
The present study aims to show compliance with Laurence Bardin’s Content Analysis technique when understanding written publications used by the humanities disciplines in High School. Considered an instrument of research which searches for different signifier and signified in messages – the background of communication – this methodology aims at making the reader more distrustful of the assumptions made in a text and aware of spontaneous or superficial reading. This research was applied in practice when teaching the subject of Sociology, at a private school in São Paulo, at the time at which determining the relevance of the methodology in everyday school conditions were aimed. The results achieved by inferences and interpretations per categories as well as those obtained by frequency or lack of information in documents served as a comparison with different text analyses which did not use the Bardin’s technique. An expressive group of students achieved relevant results throughout the copious meanings of messages acquisition, being able to assess and even deconstruct the author's intentions and its contextual conditions